MIFOLOGIYALÍQ QUS OBRAZÍNÍŃ TÚRKIY XALÍQLAR FOLKLORÍNDA ÚYRENILIWI - Kabilova, G.B. (ILIM hám JÁMIYET, 2025)
In the article, scientific-theoretical comments were made about the history of the study of the primitive mythological bird image in the folklore of Turkic peoples, its unique feature in folklore genres. Scientific opinions were given about the origin of the mythological bird image in the folklore of the people based on totem beliefs and the artistic service of this mythological image.